2014
DOI: 10.1002/sia.5442
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an induction‐assisted friction stir welding technique for super duplex stainless steels

Abstract: The microstructure changes and the mechanical properties of a friction stir welded (FSW) super duplex stainless steel (GX2CrNiMoN26‐7‐4) were analyzed. A PCBN tool was used to weld 5‐mm‐thick plates at a constant rotational speed of 300 rpm, at 100 and 200 mm/min, under two different conditions: conventional FSW and Induction‐Assisted FSW (IA‐FSW). Preheating technique allows welding with a reduction in forge forces close to 31% at the same welding speed, or doubling speed (200 mm/min) at the same axial force,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Arora et al 31 also proposed that preheating at the plunge stage can overcome a pilot hole’s need at the plunge stage. Alvarez et al 15 found that plunge force was reduced by 30% during induction assisted FSW of super duplex stainless steel. Similarly, Amini and Amiri 32 and Zhong et al 33 also reported that z force is reduced significantly during the UFSW process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Arora et al 31 also proposed that preheating at the plunge stage can overcome a pilot hole’s need at the plunge stage. Alvarez et al 15 found that plunge force was reduced by 30% during induction assisted FSW of super duplex stainless steel. Similarly, Amini and Amiri 32 and Zhong et al 33 also reported that z force is reduced significantly during the UFSW process.…”
Section: Resultsmentioning
confidence: 99%
“…The force reduction during the plunge stage is consistent with those reported in previous literature. 15,23 Sinclair et al 30 observed that the z force was less during the thermally-assisted FSW process. They observed that preheating reduced the material flow stress and eased the material transport phenomenon from AS to RS during FSW of steel alloys.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction assisted FSW (IAFSW) uses electrical inductance to generate heat to soften the workpiece materials. IAFSW has been reported for joining medium strength Aluminium alloy [18] and high strength steel [19,20]. Both researchers in [18 and 19] reported that the downward force was reduced, but mechanical properties in the joints still maintained.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By intuition, any auxiliary heating in addition to friction heating at workpiece and pin interface could improve FSW weldability, as discussed in some recent publications. [23][24][25] The present shear localization model can be used to quantitatively assess how such an auxiliary heating method would improve a material's FSW weldability in terms of shear localization parameters such as SB width, SB formation time and the resulting welding speed. The following section considers two auxiliary heating methods: one is by means of an auxiliary heat flux input at workpiece and pin interface; the other is through a pre-heating process so that a target temperature level can be achieved in weld area before FSW takes place.…”
Section: Auxiliary Heating Effectmentioning
confidence: 99%